The Effect of Boss Phubbing on Employee Engagement and Employee Performance: The Mediation Role of Trust and Job Satisfaction - Hadi Yuda, Irfan; Suyono, Joko (Program Studi S3 Ilmu Manajemen, 2024)
This research aims to investigate the influence of Boss Phubbing on Trust, Job Satisfaction, Employee Engagement, and Employee Performance. The study was carried out at the Head Office of the Ministry of Education, Culture, study and Technology in Jakarta. Data collection was done using an online survey approach, and a basic random sample strategy was used. The participants in this research were government employees who were employed in the main office of the Ministry of Education, Culture, Research and Technology in Jakarta. The research included a total of 191 participants, who were recruited via online questionnaires. The research done using SmartPLS reveals that Boss Phubbing has a detrimental effect on Trust, Employee Engagement, and Employee Performance.